Analyzing the Impact of Long-Term Financing on Cement Companies' Profitability in Indonesia Stock Exchange - Dasinapa, Margaretha Beatrik (Advances in Management & Financial Reporting, 2023)
This study aimed to determine the effect of long-term debt and equity on profitability in cement sub-sector companies listed on the Indonesia Stock Exchange. The type of data used in this study is quantitative data in the form of values or numbers obtained from financial reports. The source of data in this research is secondary data. The population in this study were manufacturing companies in the basic industrial sector and the cement sub-sector chemicals listed on the Indonesia Stock Exchange, totaling 6 companies. Using the purposive sampling method, the total sample in this study is 35 data from 6 companies. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, classic assumption tests (normality test, heteroscedasticity test, multicollinearity test), and testing of all hypotheses through a partial test (t test), simultaneous test and coefficient test determination. The results of this study indicate that long-term debt has a negative and insignificant effect on profitability. Meanwhile, own capital has a positive and insignificant effect on profitability. In addition, long-term debt and equity do not simultaneously have a significant effect on profitability.